Study and Analysis of Millimetre Wave Antenna for 5G - Hameed, Nazia; Gupta, Vipin (International Journal of Engineering and Technology, 2018)
Due to the demand of more capacity and users, 5G (next generation) of wireless will be able to handle thousands times more traffic than today it works and it will be 10X faster than today 4G LTE. There has been a great research around the world in advancing future generation 5G wireless networks. Till now 5G standards are not available for us. Some researchers have been started that will provide these standards. The 5G system will require compact but efficient antenna. The main goal of 5G is to obtain better coverage at lower cost. The technology used in 5G to attain this goal will be obtained millimeter waves. Our smart phones and other electronic devices in our homes use specific frequency on radio frequency spectrum typically those under 6 GHz but these frequencies are started to get more crowded. Carriers can only squeeze so many bits of data on same amount of radio frequency spectrum. As more devices come online we are going to see lower service and more dropped connection. The solution is to adapt some new real estate like millimeter waves. In this paper, we present the future antenna for 5G, methodology and variety of simulation results at 6.5 GHz by using HFSS software. A microstrip patch antenna is designed by using FR4-epoxy for advantages of low cost, high flexibility, harmless to human body.Â Â